El dibujo y la creatividad en niños de la Institución Educativa Inicial N° 746 Santa Clara, Caballococha 2022 - Valentin Dosantos, Marleny (2024)
The main objective of the present investigation has been to determine the relationship between drawing and creativity in children from the Institución Educativa Inicial N°746 Santa Clara, Caballococha 2022, and to achieve this, relational research was used as a type of research, with a design not experimental, correlational transectional. The population was all children from the aforementioned Institution, the sample was census, which is equivalent to 86 children. The observation technique was used and the observation guide as instruments, in order to obtain the data, the instruments were validated through expert judgment. The results of the Spearman's Rho correlation value is 0.288, it is evident that there is a moderate and significant positive relationship between drawing and creativity, which suggests that children who have better performance in drawing tend to show higher levels of creativity.